Transport Governance Indicators in Sub-Saharan Africa - Christie, Angela; Smith, Don; Conroy, Kate (World Bank, Washington, DC, 2014)
Good governance-or the absence of it-has concerned policy makers and other stakeholders in the transport sector for decades. Most stakeholders recognize that effective governance is crucial if improvements in transport infrastructure are to endure and contribute to sustainable economic growth. In Africa, billions of dollars have been spent on improving and rehabilitating transport infrastructure, but it has been long recognized that the poor performance of the transport sector is due to far more than merely inadequate finance or technical capacity constraints. Poor governance occurs at many levels of the policy cycle-from the ways in which legislation is drafted and regulations, systems, and procedures are worded and applied in practice, to how services are eventually delivered to the users of transport and whether their expectations are met. This paper sets out to identify a critical subset of governance indicators in the transport sector that can be used to demonstrate in a clear, measurable way the quality of governance in a particular country, sector, or subsector. By means of consultation with key transport sector stakeholders, it examines transport sector governance issues in four pilot countries in order to determine whether there is a consensus on what transport sector governance means in practice; why it matters; how it can be measured; and in what priority ways improvements in governance might make a real difference in the sector and its contribution to national development. At its core, the study attempts to reduce the indicator set to what is at the heart of the governance matter.